A self-crosslinking thermosetting monomer with both epoxy and anhydride groups derived from tung oil fatty acids: Synthesis and properties. (September 2015) - Huang, Kun; Liu, Zengshe; Zhang, Jinwen; Li, Shouhai; Li, Mei; Xia, Jianling; Zhou, Yonghong
Graphical abstract: Highlights: Synthesized a self-crosslinking of tung oil fatty acid with epoxy groups and anhydride groups. The compound shows excellent storage stability and is curable with trace amounts of tertiary amine. The advantage is the homogeneous during mixing of the epoxy resins and curing agents. It is a very promising bio-based epoxy resin. Abstract: A self-crosslinking compound with epoxy groups and anhydride groups (GEMA) was successfully synthesized from tung oil fatty acid by reacting with maleic anhydride via the Diels–Alder reaction. GEMA has very good storage stability and could be cured with trace amounts of tertiary amine. This advantage avoided the nonuniformity, bubbles and insolubility during the mixing procedure of the epoxy resins and curing agents. Compared to commercial Bisphenol A epoxy resins, GEMA has relatively lower mechanical properties and thermal properties. However, in view of its renewable properties, GEMA is still a very promising bio-based epoxy which may replace bisphenol A epoxy resins in some applications.